THE COST INFORMATION RELEVANCE IN THE DECISION FOUNDATION - BUMBESCU, Sorina Simona; PASCHIA (DINCĂ), Liliana (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 15 (2013): Annales Universitatis Apulensis Series Oeconomica, 2013)
In this paper is realized an overview of the existing interdependence between the decision efficiency and the cost information quality who are provided to the organization management. Based on the previous studies regarding the costs and managerial decisions, in this article is developed an lapidary theoretical framework regarding the cost- general framework, the costs needed for the decisions making, the usefulness and importance of cost information system for decision process, and ultimately is presented in a lapidary form the costs structure of the European projects.